Cerebellar Patterning Defects in Mutant Mice - Hawkes, Richard (Frontiers in Neuroscience, 2021)
The cerebellar cortex is highly compartmentalized and serves as a remarkable model for pattern formation throughout the brain. In brief, the adult cerebellar cortex is subdivided into five anteroposterior units – transverse zones – and subsequently, each zone is divided into ~20 parasagittal stripes. Zone-and-stripe pattern formation involves the interplay of two parallel developmental pathways – one for inhibitory neurons, the second for excitatory. In the inhibitory pathway, progenitor cells of the 4th ventricle generate the Purkinje cells and inhibitory interneurons. In the excitatory pathway, progenitor cells in the upper rhombic lip give rise to the external granular layer, and subsequently to the granular layer of the adult. Both the excitatory and inhibitory developmental pathways are spatially patterned and the interactions of the two generate the complex topography of the adult. This review briefly describes the cellular and molecular mechanisms that underly zone-and-stripe development with a particular focus on mutations known to interfere with normal cerebellar development and the light they cast on the mechanisms of pattern formation.